Red blood cell distribution width as a predictor of mortality in critically ill pediatric patients: a systematic review and meta-analysis - Yu, Yinhong; Hu, Xiaomei; Shen, Yaping (Frontiers in Pediatrics, 2025)
ObjectiveRed blood cell distribution width (RDW) has been found to predict outcomes in critically ill adult patients. However, its utility in pediatric patients remains unexplored. We reviewed published evidence and conducted a meta-analysis to assess whether RDW can be used to predict mortality in the pediatric intensive care unit (PICU).MethodsAll observational studies assessing the association between RDW and PICU mortality available on the databases of PubMed, Embase, Scopus, and Web of Science up to 4th November 2024 were included. A detailed review of study outcomes was conducted with a meta-analysis.ResultsSeven studies were included. 6,327 pediatric patients were included in these studies. On qualitative analysis, five of the seven studies found a statistically significant association between high RDW and PICU mortality. Four studies used RDW as a continuous variable, while three studies reported specific RDW cut-offs. Meta-analysis showed that an incremental increase in RDW was associated with a statistically significant increased risk of mortality (OR: 1.24 95% CI: 1.07, 1.44 I2 = 32%). Pooled analysis of studies using RDW as a categorical variable showed that higher values of RDW were associated with significantly higher risk of mortality (OR: 1.73 95% CI: 1.02, 2.92 I2 = 77%).ConclusionsRDW could be a potential predictor of mortality in the PICU. Results need to be interpreted with caution owing to the limited number of studies with variable study populations. Additional studies are needed to strengthen evidence.Systematic Review RegistrationPROSPERO (CRD42024606208).